2015
DOI: 10.3844/ajessp.2015.62.75
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Geographic Information System-Based Assessment Model for Sustainable Metropolitan Development: The Case of the Semarang Metropolitan Region, Indonesia

Abstract: Spatial dynamics of metropolitan development are becoming important issues in sustainable development. In developing countries like Indonesia, the growth of metropolitan regions is often followed by problems of unsustainability. Therefore, a framework of assessment for metropolitan development can be useful as an early means of identifying any untoward aspects. This study aims to develop an assessment system that is easily applicable (user-friendly) in assessing metropolitan development in Indonesia. It is a G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Relocalization and spatial decentralization, as encouraged by the eco-village concept, are often considered automatically able to lead to long-term sustainability. However, there are problems at the urban and metropolitan levels also in need of a variety of improvement strategies, among which are those developed in the model of sustainable metropolitan development for Semarang [28]. It is not surprising then that Xue proposed and demonstrated that multi-scalar strategies considering the multifaceted relation between typical social transformation and spatial development are needed to ensure sustainable urban development.…”
Section: Methodsmentioning
confidence: 99%
“…Relocalization and spatial decentralization, as encouraged by the eco-village concept, are often considered automatically able to lead to long-term sustainability. However, there are problems at the urban and metropolitan levels also in need of a variety of improvement strategies, among which are those developed in the model of sustainable metropolitan development for Semarang [28]. It is not surprising then that Xue proposed and demonstrated that multi-scalar strategies considering the multifaceted relation between typical social transformation and spatial development are needed to ensure sustainable urban development.…”
Section: Methodsmentioning
confidence: 99%
“…The concept of Equity-Based (Regional) Development (EBRD) by Sugiri (2009) can address the challenges of sustainability, particularly for resource-rich economies like Indonesia. Studies applying the concept have been on various issues, from spatial inequality (Sugiri and Nuraini, 2013), in which the researchers have found that it is inequity that should be addressed first to resolve the spatial inequality problem, to sustainability assessment of the Semarang metropolitan development (Buchori et al, 2015).…”
Section: Ensuring Sustainability Through Equity-based Developmentmentioning
confidence: 99%
“…In recent development, Semarang faces various complex environmental problems, such as flood and inundated area [20,21]. The inundated area, climate hazard and other environmental issues in Semarang is tend to increase have an impact on the deterioration of the quality of the environment.…”
Section: Study Area and Issuesmentioning
confidence: 99%